2021
DOI: 10.3390/pathogens10040466
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of Clinical Candida Isolates

Abstract: The factors enabling Candida spp. infections are secretion of hydrolytic enzymes, adherence to surfaces, biofilm formation or morphological transition, and fitness attributes. The aim of this study was to investigate the correlation between known extracellular virulence factors and survival of Galleria mellonella larvae infected with clinical Candida. The 25 isolates were tested and the activity of proteinases among 24/24, phospholipases among 7/22, esterases among 14/23, hemolysins among 18/24, and biofilm fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 64 publications
4
25
1
5
Order By: Relevance
“…Aspartate protease and lipase production as well as hemolytic activity are well known extracellular virulence factors in case of the opportunistic pathogen Candida species [57], yet, in our study, mycosis isolates did not show higher activities in most factors, only in β-hemolysis after 3 days. In the case of α-hemolysis measured after 1 day, the commercial isolates showed higher activity.…”
Section: Discussioncontrasting
confidence: 67%
“…Aspartate protease and lipase production as well as hemolytic activity are well known extracellular virulence factors in case of the opportunistic pathogen Candida species [57], yet, in our study, mycosis isolates did not show higher activities in most factors, only in β-hemolysis after 3 days. In the case of α-hemolysis measured after 1 day, the commercial isolates showed higher activity.…”
Section: Discussioncontrasting
confidence: 67%
“…Also, all the inoculated organisms proved pathogenicity with varying degrees of virulence, and they were reisolated from the inoculated fish and isolated on specific media. Candida parapsilosis is a pathogenic strain that revealed the occurrence of 76% mortalities; this could be returned to the expression of haemolysins, proteases and esterases as recently reported by Mroczyn´ ska and Brillowska‐Da˛browska (2021). Similarly, Eissa et al (2013) and Tartor et al (2018) also described the pathogenicity of C .…”
Section: Discussionmentioning
confidence: 56%
“…Although phospholipases possess target phospholipid substrates, their classification is based on the specific ester bond they target [ 56 ]. In this sense, C. albicans owns phospholipases A, B, C and D, but until now only few members of phospholipase B are known to be secreted to the environment [ 57 ]. In vivo experiments demonstrated that the absence of phospholipase B resulted in the attenuation of virulence of C. albicans in a murine model of disseminated candidiasis [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Esterases, another class of lipolytic enzymes, can hydrolyze the ester bonds of mono-, di- and triacylglycerols into alcohol and acid, acting better on soluble substrates [ 48 ]. Esterases are involved in lipid digestion for nutritional purposes, and during the infection they participate in the adhesion process and invasion of epithelial cells [ 57 ]. Our results showed that esterase activity was quite similar to the phospholipase activity, with 85.7% (6/7), 81.8% (9/11) and 71.4% (5/7) of isolates exhibiting weak activity for C. haemulonii , C. duobushaemulonii and C. haemulonii var.…”
Section: Resultsmentioning
confidence: 99%